Pengaruh Social Media Marketing melalui Media Instagram terhadap Brand Equity Hotel Sthala A'Tribute Portofolio Ubud. - Maharani Amanda, Ni Kadek Nandita; Gede Witarsana, I Gusti Agung; Adyatma, Prastha (Program Studi Administrasi Perhotelan, 2025)
The creation of a company's branding is an effort to attract the attention of potential buyers. In the current era of globalization, one of the most common marketing activities is online marketing, including through social media marketing. This research was conducted at Hotel Sthala A, Tribute Portfolio, Ubud Bali. The aim of this research is to determine the influence of Instagram social media marketing on brand equity at Hotel Sthala A, Tribute Portfolio, Ubud Bali, analyzed using the Statistical Program for Social Science (SPSS). The type of data required by the researcher is quantitative associative data. The population in this study involves active Instagram users who have followed and viewed content shared by the Hotel Sthala A, Tribute Portfolio, Ubud Bali Instagram account. The sample used in this study consists of 100 respondents who are active Instagram users who have followed and viewed content shared by the Hotel Sthala A, Tribute Portfolio, Ubud Bali Instagram account. The sampling technique used is non-probability sampling with a purposive sampling approach. The results of this study indicate that Instagram social media marketing has a positive and significant effect on brand equity at Hotel Sthala A, Tribute Portfolio, Ubud Bali.